UTILISATION OF PLASTIC WASTE TO PRODUCE ECO-FRIENDLY FOUNDATION MATERIAL FOR HOUSEHOLD ORGANIZER - ZAINAL ABIDIN, ANIS SAKINAH; AHMAD KURNIN, NOR AZRIN; SAMAT, SUHAILAH (MALAYSIAN JOURNAL OF INNOVATION IN ENGINEERING AND APPLIED SOCIAL SCIENCES (MYJIEAS), 2024)
Plastics are a form of synthetic organic polymers and are one of the most often used materials because they are durable, lightweight, flexible and relatively affordable to manufacture. With the global transition from reusable to single-use containers, the demand for packaging materials has surged. Thus, this have led to high contribution of plastic waste in the world. Thus, this project focused on utilizing plastic waste specifically High-Density Polyethylene (HDPE) and Polypropylene (PP) to produce eco-friendly foundation material for household organizer by using green approach. The second objective is to find the optimum mixing ratio of PP and HDPE to produce the foundation material. The product is then tested for its’ mechanical property specifically tensile strength prior to constructing the final product which is organizer. PP and HDPE are obtained by collecting waste detergent bottles, supplement bottles and drinking waste bottle caps. Both materials are washed, dried and cut into small pieces before undergo heat treatment using hot press. Melted plastics are then molded into specific shape for mechanical testing. Tensile test and Young Modulus results of 7.63 MPa and 13.996 MPa respectively, indicate that a mixing ratio of 2PP: 8HDPE is sufficient to be used for constructing household organizer foundation material.